Redes de cooperación en la producción académica en el campo de las neurociencias: un estudio bibliométrico (2018)
The neurosciences and the variations in the dynamics of cooperation in research, are two important phenomena that have been gaining strength in recent years with scientific advance. The objective of this research is to analyze how cooperation networks affect academic production in the field of neurosciences in Colombia through comparison with other Latin American countries. The Scopus database was used as a source of information, covering the data from 1971 to 2016, to generate landscapes of scientific visualization that gave an account of the dynamics of cooperation among countries, institutions and authors, as well as allowing us to glimpse the main areas of approach of the authors of the neurosciences. There is a Latin American tendency to the study of Alzheimer's and epilepsy, as well as some "diaphanous" cooperation dynamics in Colombia in comparison with countries of high production, however, inconsistencies in the research dynamics in the country that require new regulation methodologies.